2020
DOI: 10.18632/oncotarget.27338
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mutations and overall survival in 3,084 patients with cancer: the Hellenic Cooperative Oncology Group Precision Medicine Initiative

Abstract: Copyright: Fountzilas et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACTBackground: We evaluated the association between pathogenic mutations and overall survival (OS) in patients with cancer referred to Hellenic Cooperative Oncology Group-affiliated Departments.Patients and methods: Patients refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Mutated MLL3 (or KMT2C) proteins have been implicated in multiple cancers, including urothelial carcinoma, human lymphoid, and myeloid leukemia [ 46 , 47 , 48 ]. Further, we found that NSCLC patients with FANCA mutations had significantly worse OS compared to those without FANCA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Mutated MLL3 (or KMT2C) proteins have been implicated in multiple cancers, including urothelial carcinoma, human lymphoid, and myeloid leukemia [ 46 , 47 , 48 ]. Further, we found that NSCLC patients with FANCA mutations had significantly worse OS compared to those without FANCA mutations.…”
Section: Discussionmentioning
confidence: 99%